Staatsgalerie Augsburg : Altdeutsche Malerei in der Katharinenkirche - Schawe, Martin; Staatsgalerie am Schaezler-Palais (Augsburg, Germany); Bayerische Staatsgemäldesammlungen (München : Bayerische Staatsgemäldesammlungen, 2001)
Aldeutsche Malerei in der Katharinenkirche
Includes bibliographical references (p. 113-[117]).
Keywords: Painting, German -- 15th century -- Catalogs; Painting, German -- 16th century -- Catalogs; Painting -- Germany -- Augsburg -- Catalogs; Staatsgalerie am Schaezler-Palais (Augsburg, Germany) -- Catalogs